2017
DOI: 10.20959/wjpr20174-8050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phytochemical, Antioxidant and Microbial Property of Various Extracts of the Plant Melilotus Indica

Abstract: Melilotus indica is a plant commonly known as 'Banmethi' inBangladesh. It is a herb which has long been used traditionally for various medicinal purposes in all over the world. Being the member of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
3
4
0
Order By: Relevance
“…Other studies on the species of genus Euphorbia and Melilotus have confirmed the efficacy of the methanolic extracts compared with the aqueous extracts. The methanolic extracts showed high antimicrobial activity against various pathogenic microorganisms, also, the methanolic extracts displayed larger inhibition zones against Gram-positive bacteria compared to Gram-negative bacteria (Naz et al, 2017;Lone et al, 2013;Sonju et al, 2017). The results of the present study are consistent with the above studies conducted on species belong to the selected genera in this study.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Other studies on the species of genus Euphorbia and Melilotus have confirmed the efficacy of the methanolic extracts compared with the aqueous extracts. The methanolic extracts showed high antimicrobial activity against various pathogenic microorganisms, also, the methanolic extracts displayed larger inhibition zones against Gram-positive bacteria compared to Gram-negative bacteria (Naz et al, 2017;Lone et al, 2013;Sonju et al, 2017). The results of the present study are consistent with the above studies conducted on species belong to the selected genera in this study.…”
Section: Resultssupporting
confidence: 91%
“…The agar well diffusion assay has been used in this research because it is more sensitive than the agar disc diffusion assay (Valgas et al, 2007). Many studies have shown that extracts obtained from the Euphorbia and Melilotus genera inhibit the growth of different microorganisms at various concentrations (Annapurna et al, 2004;Singh & Kumar, 2013;Sonju et al, 2017;Sisay et al, 2019). Other studies on the species of genus Euphorbia and Melilotus have confirmed the efficacy of the methanolic extracts compared with the aqueous extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, Miet showed moderate radical-scavenging potential, which is suggested to be due to its multiple phytochemicals, i.e., quercetin as well as coumarin. 19 In the present study, tumor-bearing animals showed dose-dependent effects after treatment with Miet 50% and 25%. In addition, levels of tumor yield, tumor burden, cumulative number of tumor, and tumor incidence were significantly decreased in the Miet 50% treatment group and approached almost normal values, hence indicating the excellent therapeutic capability of Miet against skin cancer ( Tables 2 and 3 ).…”
Section: Discussionsupporting
confidence: 53%
“…It has been traditionally used as an antispasmodic, emollient, analgesic, and astringent agent since ancient times. 10 Data of several in vitro studies revealed that M. indicus (L.) All. shows cytotoxic activity against different cancerous cell lines due to its various properties.…”
Section: Introductionmentioning
confidence: 99%